The resurrection of Jesus in its Jewish context - Crossan, John Dominic (Neotestamentica, 2003)
Perfectly valid and important historical questions may be raised about the burial of Jesus, the discovery of his empty tomb, the apparitions to his companions (if, where, when, why, etc.), and the purpose of those latter stories in their present gospel contexts. In this article those questions are temporarily bracketed and, however integrated, the gospel stories are stipulated as factually given and accepted as historically accurate (dato non concesso, of course). The purpose of this temporary strategy is to raise three more fundamental questions. First, what, be it in belief or disbelief, did a first-century Jew mean by "resurrection." Second, what, against that background, did a first-century Christian Jew mean by claiming that God had raised Jesus from the dead? Third, in a pre- Enlightenment world where such wonders were culturally and permanently possible, why would anyone (especially a pious pagans) have cared?